Implementation of Screening for Child Growth and Development - Heri Saputro; Septiana Rahmawati; Murtiningsih Murtiningsih; Nugroho Zahrowaana Muslim; Ferdinand Arinto Kadege (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2019)
Growth occurs simultaneously with development. In contrast to growth, development is the result of the interaction of the maturity of the central nervous system with the organs it influences, for example the development of the neuromuscular system, speech, emotions and socialization. The implementation of this activity was carried out at the Permata Playhouse in Kediri City. Activities are carried out in a day. Activities are carried out using weight scales, microstructure, and child development questionnaires. From the results, some children experience delays in growth and development. The importance of the role of parents and health workers in monitoring and preventing growth and development problems